Energy Efficiency and Decarbonization Resulting from the Transition to Virtual Space - Viktoria Mannheim; Zsuzsa Szalay; Renáta Bodnárné Sándor; Anita Terjék; Judit Lovasné Avató; Péter Sasvári; Zsolt István; Artúr Szilágyi; Orsolya Szalainé Kaczkó; Klára Tóthné Szita (Energies, 2025)
It is a serious challenge for humanity to find an appropriate response to stop the accelerating rise in global temperature caused by atmospheric carbon dioxide emissions. After a methodological review of the literature, online and in-person modelling of education, work, and conferences, and relying on the results of life-cycle studies, we sought the answer to what reasonable solutions are available for decarbonization and energy reduction. During the research, the organizational carbon footprint of a selected office, educational institution and conference, and then the carbon footprint created by a person in 1 h, were examined. The two-day online education significantly reduced the daily commute load in transport by 402 tons of CO2 equivalent per year. Still, the energy demand of home learning subtracts 136 tons from this, so the real benefit was 266 tons above in an institution educating nearly 3500 students. In a workplace of 180 people, where 52% of employees commute, 90% teleworking saved 222 tons of carbon dioxide emissions in one month, taking into account the carbon footprint of working from home. In the case of conferences, the online solution reduces the carbon footprint due to the absence of travel and catering. Comparing the three areas, for the in-person case, the conference’s carbon footprint per person per hour was the highest (11.91 kg CO2 eq.). This value for education was 1.15 kg CO2 eq.; for work, it was the lowest with a value of 0.90 kg CO2 eq. Moving to an online space resulted in the most significant savings for the conference (11.55 kg CO2 eq.), followed by working (0.54 kg CO2 eq.), and minor savings were achieved in hybrid education (0.13 kg CO2 eq.). The sensitivity analysis highlighted the impact of transport on carbon footprint in all three cases. However, the life cycle cost analysis showed that moving to a virtual space reduces the life cycle cost of de-carbonization by 42%.